Transition and Transgression : English Young Adult Fiction in Post-Apartheid South Africa (Emerging Perspectives: Interdisciplinary Graduate Research in Education and Psychology, 2019)
The book “Transition and Transgression – English Young Adult Fiction in Post-Apartheid South Africa” is an effort by Judith Inggs to counter the dearth of information on English literature for the youth in South Africa. As an intended resource for educators, teachers and researchers, the book is written with the underlying premise that “literature for young adults often illustrates and reflects changes taking place in society” (p.1). Emphasizing how young adults view societal institutions that affect their lives and how they negotiate and identify themselves with respect to positions of power, the author provides relevant titles and content of literary texts as examples while critically analyzing their value from an educational perspective.